2014
DOI: 10.1109/access.2014.2364638
|View full text |Cite
|
Sign up to set email alerts
|

A 15-Gb/s Wireless ON-OFF Keying Link

Abstract: Bit-error rate measurements for ON-OFF keying modulation at multigigabit per second rates over a V-band wireless link are presented. Serial data-rates from 2.5 to 20 Gb/s were studied for a 2 31 -1 bit random sequence. Error-free data transfer over a 0.3-m link was achieved at up to 10 Gb/s. Acceptable bit-error rates, <10 −5 and 10 −3 , were measured at up to 1.5 m for 10-and 15-Gb/s datarate, respectively. The performance was achieved using a transmitter that consists of an integrated wavelet generator, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…3, is and estimates the attenuation constant of the material. Using the attenuation constant and , the imaginary part of the refractive index is estimated to (3) where the refractive index in (3) is approximated as for low-loss materials. The resulting permittivity is , which is, as expected, the same as the permittivity assigned to the material.…”
Section: Direct Time-domain Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, is and estimates the attenuation constant of the material. Using the attenuation constant and , the imaginary part of the refractive index is estimated to (3) where the refractive index in (3) is approximated as for low-loss materials. The resulting permittivity is , which is, as expected, the same as the permittivity assigned to the material.…”
Section: Direct Time-domain Extraction Methodsmentioning
confidence: 99%
“…I N RECENT years, there has been an increasing interest in applications at millimeter-wave (mm-wave) frequencies due to the existence of unlicensed bands for a variety of applications in radars, imaging, medical, and wireless communications [1]- [3]. From tomography in medical applications to channel modeling in wireless communications, the knowledge about material properties is essential.…”
Section: Introductionmentioning
confidence: 99%
“…P .0/ P .1/ D 1: 0 (15) In the case when the t location-scale distribution is used, one has the detector as follows: where f t . P .0/ P .1/ D 1: 0 (15) In the case when the t location-scale distribution is used, one has the detector as follows: where f t .…”
Section: Novel Receiver Derivationmentioning
confidence: 99%
“…Each h i is a complex Gaussian random variable with mean zero and variance 2 2 h . Because of simplicity and low power requirement, on-off keying signal, which is widely used in both radio frequency [15,16] and freespace optical communications [17,18], is a simple signal suitable for noncoherent energy detection that aims for extending the network coverage. The total number of relays is N 1.…”
Section: Signal Modelmentioning
confidence: 99%
“…Due to the high dielectric constant of the substrate, the radiated power is directed mostly in the substrate and is therefore extracted from the substrate backside through a Si-collimation lens. Earlier, Ohlsson et al reported a 15 Gbps over 1.5 m wireless link using an RTD-MOSFET wavelet generator [7]. A 62.5 GHz single RTD source with 3.2 mW output power was integrated with 130 nm III-V MOSFET switch through which the source was modulated.…”
Section: Introductionmentioning
confidence: 99%